Synthesis and Properties of Red Mud-Based Nanoferrite Clinker. (29th July 2019) - Sun, Hongfang; Chen, Chuyu; Ling, Li; Memon, Shazim Ali; Ding, Zhu; Li, Weiwen; Tang, Lu-ping; Xing, Feng
Abstract : Red mud, an industrial waste obtained from alumina plants, is usually discharged into marine or disposed into a landfill polluting the surrounding water, atmosphere, and soil. Thus, disposal of red mud is an environmental concern and it should be recycled in an effective way. Since red mud consists of iron- and aluminum-rich phases, it can potentially be processed into cementitious material and can be used for a construction purpose. This research investigated the synthesis of nanoferrite (NF) clinker by using red mud as a raw material through chemical combustion technology for potential use in cement-based composite. Before the synthesis of NF, red mud was characterized by using XRF, XRD, and SEM techniques. From characterization results, the stoichiometric ratio of raw materials was calculated and experimentally optimized. The sample was then tested at various temperatures (815, 900, 1000, and 1100°C) to find the optimum synthesis temperature. Finally, the hydraulic activity of NF was verified and the contribution to mechanical properties was determined by replacing cement with NF at various substitution levels (0, 5, 10, and 20 wt%). Test results showed that the optimum condition for the synthesis of NF was found when the ratio of CaCO3 /red mud was 1.5 and the sintering temperature was 815°C. The synthesized NF had an average diameter of 300 nm, and the main composition was brownmillerite (C4 AF) with distinct hydraulic reaction. When NF was used as a substitute of Portland cement in mortar, the flexural strength with a 5% replacement level improved by 15%. Therefore, it can be concluded that the synthesis of NF provides an alternative approach to recycle red mud and could significantly help in reducing environmental pollution.